2019
DOI: 10.1002/wmon.1039
|View full text |Cite
|
Sign up to set email alerts
|

Roles of maternal condition and predation in survival of juvenile Elk in Oregon

Abstract: Understanding bottom‐up, top‐down, and abiotic factors along with interactions that may influence additive or compensatory effects of predation on ungulate population growth has become increasingly important as carnivore assemblages, land management policies, and climate variability change across western North America. Recruitment and population trends of elk (Cervus canadensis) have been downward in the last 4 decades across the northern Rocky Mountains and Pacific Northwest, USA. In Oregon, changes in vegeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 165 publications
2
32
1
Order By: Relevance
“…Vital rates that dictate population change are pregnancy, age of first reproduction, juvenile survival, and adult survival ( Gaillard et al 2000 )—all of which are linked to nutrition to varying degrees depending upon the species and the environment. For example, body fat was linked strongly to probability of pregnancy in caribou ( Gerhart et al 1996 ), moose ( Testa and Adams 1998 ), and to timing of breeding and thus parturition in elk ( Cook et al 2004 ; Johnson et al 2019 ). Tollefson et al (2010 ) observed that body fat predicted the probability of twinning in mule deer.…”
mentioning
confidence: 99%
“…Vital rates that dictate population change are pregnancy, age of first reproduction, juvenile survival, and adult survival ( Gaillard et al 2000 )—all of which are linked to nutrition to varying degrees depending upon the species and the environment. For example, body fat was linked strongly to probability of pregnancy in caribou ( Gerhart et al 1996 ), moose ( Testa and Adams 1998 ), and to timing of breeding and thus parturition in elk ( Cook et al 2004 ; Johnson et al 2019 ). Tollefson et al (2010 ) observed that body fat predicted the probability of twinning in mule deer.…”
mentioning
confidence: 99%
“…There is no pretense that pumas limit their density so as not to reduce the abundance of their food supply. To the contrary, under certain circumstances pumas do so (Logan and Sweanor , Robinson et al , Johnson et al , Johnson et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Puma predation is expected to influence ungulate populations in different ways depending upon environmental conditions and interactions of pumas with different prey and predator populations (Logan and Sweanor ; Robinson et al ; Kortello et al ; Elbroch et al , b ; Johnson et al ). Ultimately, the effect of puma predation on prey population growth will depend on the extents that predation is additive or compensatory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ungulate demography also needs to be evaluated to determine if changes in carnivore abundance result in changes in ungulate vital rates, and, ultimately, growth rate. If ungulate populations are limited by factors such as weather or habitat (Garrott et al 2003, Griffin et al 2011, Johnson et al 2019), or if predation is compensatory with other factors (Singer et al 2003, Garrott et al 2008), changes in carnivore populations may not result in changes in the key vital rates, such as recruitment, that drive ungulate population growth rate. The efficacy of integrated carnivore‐ungulate programs may be evaluated by monitoring these key ungulate vital rates and population growth pre‐ and post‐harvest treatment.…”
Section: Introductionmentioning
confidence: 99%